2019
DOI: 10.2528/pierm18121404
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Uwb Amc Antenna for Early Stage Skin Cancer Identification

Abstract: This work involves designing an antenna that meets the requirements of radar systems. The associated technology, which was for a long time reserved for the military field, is now available in the civil field, as well as in the biomedical sector for the development of "monitoring" systems allowing to monitor the state of health of a patient in a non-invasive way. The goal of this article is to design a wearable textile antenna to detect cancerous tumors of a patient without direct contact with the skin taking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 14 publications
(21 reference statements)
0
30
0
Order By: Relevance
“…In [85], Mersani et al introduced a compact monopole antenna to diagnose skin cancer in a person afflicted by xeroderma pigmentosum diseases for use in radiography. The proposed antenna reacted successfully with the specified criteria and showed UWB behavior.…”
Section: Bending Scenarios In Wearable Antennasmentioning
confidence: 99%
See 1 more Smart Citation
“…In [85], Mersani et al introduced a compact monopole antenna to diagnose skin cancer in a person afflicted by xeroderma pigmentosum diseases for use in radiography. The proposed antenna reacted successfully with the specified criteria and showed UWB behavior.…”
Section: Bending Scenarios In Wearable Antennasmentioning
confidence: 99%
“…Section 2 investigated the performance of textile wearable antennas with respect to their size, substrates, and frequency bands [29, 37, 42-44, 46, 57, 59, 60]. Furthermore, the bending scenarios of antennas in several radiuses and the impact of bending on the efficiency were addressed in Section 3 [59,67,70,71,73,79,85,[91][92][93]. On the other hand, Section 4 exposed the high conductive substrate materials and discussed their effect on the design and fabrication of different wearable antennas [111, 115-119, 124, 125, 132].…”
Section: Introductionmentioning
confidence: 99%
“…Wearable technology is a growing area of innovation that can reduce medical mistakes and enhance the standard of patient healthcare. To diagnose skin cancer in a person afflicted by xeroderma pigmentosum disease, Mersani et al [52] suggested a miniature monopole antenna for use in medical imaging to discover the cancerous tumors without contacting the skin concerning the electromagnetic signal radiated towards the human body. The overall dimension of the antenna was defined as shown in figure 18 based on flexible Zelt, tin/copper textile substrate material.…”
Section: Uwb Off-body Antenna Configuration a Monopole Antennasmentioning
confidence: 99%
“…Section III concentrates on (ON-Body) communication antenna analysis and applications [70]- [86]. On the other hand, the paper classified and considered the operating frequency bands standard by 802.15 family and Federal Communications Commission (FCC) [32] UWB for OFF-Body based monopole [33], [34], [36], [40], [42]- [44], [47]- [49], [52], [54], [55], ground plane [57], [58], [63], [68] and ON-Body antennas [71], [74]- [77], [79], [81], [84]- [86]. Finally, the conclusion of the whole article is presented in section IV.…”
Section: Introductionmentioning
confidence: 99%
“…Despite detecting a tiny tumor having high resolution, the antenna system was complex, and the RF components were expensive at those high frequencies compared to the microwave region RF components [14]. A flexible AMC antenna designed for early detection of skin cancer was designed at the X-band and frequency range of 8-12 GHz, the radiation efficiency of 65%, and maximum gain of 6.5 dBi (limited bandwidth so a low resolution was obtained) [15]. Another AMC wearable UWB antenna was designed at the X-band from 8 GHz to 13 GHz to detect a tumor in the skin.…”
Section: Introductionmentioning
confidence: 99%